Actual hazard of methyl bromide fumigation in soil disinfection. - Van Den Oever, R U (1982)
Methyl bromide, a highly toxic and ready penetrating fumigant, is widely used against rodents, insects, mites, and a range of pathogenic organisms in soil, compost, and timber. To disinfect soil in greenhouses, methyl bromide is brought under pressure from outside by a vaporiser and blown on to ground under a polyethylene cover. The gas being three times heavier than air easily penetrates the ground. Depending on the local ventilation, a considerable amount of gas evaporates into the surrounding atmosphere, this emission being especially serious during the fumigation procedure and at the removal of the plastic cover. Previously, mechanical injection of methyl bromide on to the ground within closed areas was prohibited, since this technique exposed at least four disinfection workers at a time, who were provided with only a canister respirator, to gas concentrations of over 1000 ppm CH3Br. The present study established that fumigation with methyl bromide also carries risks for the well-protected worker inside, as well as for the one controlling the vaporiser. The concentration during application varies from 30 to 3000 ppm. Concentration in the air declines with time to 4 ppm CH3Br five days after application. Discarding the plastic sheet involves exposure to peak values as high as 200 ppm for a few seconds. On the ninth day after application, milling the soil can expose workers to up to 15 ppm; on the eleventh day no CH3Br concentration in the air could be found.